Selective Nanodecoration of Modified Cyclodextrin Crystals with Gold Nanorods - (:unkn) unknown (Academic Press, 2013)
Gold nanorods (AuNRs) stabilized by cetyltrimethylammonium bromide (CTAB) were deposited onto crystals of alpha-cyclodextrin (alpha-CD) inclusion compounds (ICs) that contained octanethiol (OT) as guest molecules. The nanodecoration was produced specifically at the {001} crystal planes through interaction between the -SH groups of the ICs and the AuNRs. (C) 2012 Elsevier Inc. All rights reserved.